2021
DOI: 10.1002/mp.14848
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated multicontrast reconstruction for synthetic MRI using joint parallel imaging and variable splitting networks

Abstract: Purpose Synthetic magnetic resonance imaging (MRI) requires the acquisition of multicontrast images to estimate quantitative parameter maps, such as T1, T2, and proton density (PD). The study aims to develop a multicontrast reconstruction method based on joint parallel imaging (JPI) and joint deep learning (JDL) to enable further acceleration of synthetic MRI. Methods The JPI and JDL methods are extended and combined to improve reconstruction for better‐quality, synthesized images. JPI is performed as a first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…12,[22][23][24] Recently, it has been shown that integrating PI methods into deep neural networks has the potential to improve the reconstruction quality of accelerated MRI acquisitions. [24][25][26][27][28][29][30][31] Additionally, several studies have implemented various forms of spatiotemporal convolutions for deep neural networks to exploit temporal information. [32][33][34][35] Inspired by these approaches, we propose a reconstruction method that combines joint parallel imaging (JPI) and joint deep learning (JDL) with spatiotemporal convolutions.…”
Section: Introductionmentioning
confidence: 99%
“…12,[22][23][24] Recently, it has been shown that integrating PI methods into deep neural networks has the potential to improve the reconstruction quality of accelerated MRI acquisitions. [24][25][26][27][28][29][30][31] Additionally, several studies have implemented various forms of spatiotemporal convolutions for deep neural networks to exploit temporal information. [32][33][34][35] Inspired by these approaches, we propose a reconstruction method that combines joint parallel imaging (JPI) and joint deep learning (JDL) with spatiotemporal convolutions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that prior to DL reconstruction, using parallel imaging methods resulted in improved reconstruction. 35,36 We believe that these types of methods might have the potential to improve the current state of the DL architecture for MRI reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…By applying a deep learning‐based reconstruction to the base images before parameter fitting, the resulting parameter maps and synthetic images also exhibit less noise without any additional bias 74 . Networks have also been trained to jointly reconstruct the multiple contrast base images acquired by MDME, 75 which can reduce artifacts and improve SNR over standard parallel imaging techniques. These advanced reconstruction techniques increase the effective SNR efficiency of the MDME sequence, potentially reducing scan time and enabling new applications that were previously SNR challenged.…”
Section: Future Directionsmentioning
confidence: 99%
“…After an inversion pulse, four acquisitions are acquired in a similar manner to the Look-Locker technique. Cardiac imaging is possible when the five acquisitions are triggered, resulting in equally spaced acquisition times acquired by MDME,75 which can reduce artifacts and improve SNR over standard parallel imaging techniques. These advanced reconstruction techniques increase the effective SNR efficiency of the MDME sequence, potentially reducing scan time and enabling new applications that were previously SNR challenged.…”
mentioning
confidence: 99%